Morphological phylogenetic analysis of seven varieties of ficus deltoidea jack from the Malay Peninsula of Malaysia - Nur Fatihah, Hassan; Abd Manaf, Ali; Nashriyah, Mat; Zaimah, Ab Rahman (2012)
This study is the first report to suggest a morphological phylogenetic framework for the seven varieties of Ficus deltoidea Jack (Ficus Moraceae) from the Malay Peninsula of Malaysia Sewsl molecular-based classifications on the genus Ficus had been proposed but neither had discussed the relationship between seven varieties of F deltoidea to its allies not within the varieties The relationship between seven varieties of F deltoidea is still debated due to the extreme morphological variabilities and ambiguous boundanes between taxa Thus the correct identification of these varieties is important as several morphological characters are variety-specific To test the monophyty and further (naked the relationship in F deltoidea a morphological phylogenetic analysis was conducted based on herbarium specimens representing the seven varieties of F deltoidea that were collected from the Malay Peninsula of Malaysia by using related species of the genus Ficus. F grossulariades F ischnopoda and F oleifolia as the outgroups Parsimony and neighbour-pining analyses indicated that F deltoidea is monophyletic in that the seven varieties of F deltoidea nested into two ClaCIOS dada subspecies deltoidea deltoidea Vaf bilobata. var angustRolia var kunstlen and var trengganuensis) and dada subspecies motteyana (var intermedia and var motleyana) 0 2012 Fathah et al Indexed keywords EMTREE medical terms: analytic method: anicle: cladistics. classification. Ficus Ficus angusublia: Ficus bilobata. Ficus deltoidea. Ficus grossularoides. Fkus imermedia Ficus ischnopoda Ficus kunstlen. Ficus motleyana. Ficus &Saha Ficus trengganuensis genus Malaysia molecular genetics monophyly. neighbour Joining analysis nonhuman parsimony analysis phylogeny. plant structures taxonomy MeSH: Ficus Geography Malaysia Phylogeny. Quantnathe Trait Heritable iefecLre fa the source for the MeSin terms of this document